Extreme Programming Method Utilization to Develop a Mobile-Based Reservation Application - Gabriel Nicolas Sumampow; Agus Suhendar (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Several factors, such as the surge in the number of customers during the weekends, pose a considerable challenge for the staff when it comes to reservation management. Gravito Coffee still provides conventional reservation services, including the requirement for customers to physically visit Gravito Coffee to make a reservation, and the crowded environment often makes it difficult for customers to do so. Moreover, the absence of information media results in a lack of information available to the customers, and the reservation process is still reliant on manual bookkeeping. Therefore, a system is needed to enhance the efficiency of the reservation process. The reservation system at Gravito Coffee is a mobile-based system, utilizing mobile technology to simplify information retrieval. In the development process, this system employs the Extreme Programming (XP) method with an Object-Oriented approach. The stages of this method begin with planning, coding, and testing stage using black box testing. Additionally, this system can have a significant impact on the advancement of the field of computer science. Based on the results of the implemented method and system testing, the created mobile-based reservation system can help customers make reservation, thereby increasing time efficiency and assisting waiters in taking notes. It is hoped that this application will make the process of ordering at the cafe more convenient for customers, and it is expected that this ease of ordering will also contribute to increasing customer satisfaction.